Competing interactions and the effects of uniaxial out-of-plane perturbations in the honeycomb antiferromagnet Na2⁢Co2⁢TeO6 - Arneth, Jan Victor; Kalaivanan, R.; Sankar, R.; Choi, Kwang-Yong; Klingeler, Rüdiger (Physical review materials, 2025)
Despite exhibiting magnetic long-range order below 𝑇N=26.7K, the honeycomb cobaltate Na2⁢Co2⁢TeO6 is predicted to enter a Kitaev spin liquid state when subjected to small external perturbations. While most of the reported literature investigates the effects of magnetic fields applied parallel to the honeycomb layers, we present high-resolution capacitance dilatometry studies for fields perpendicular to the Co-planes up to 15 T. Grüneisen analysis reveals the effect of uniaxial out-of-plane strain and shows that antiferromagnetic order in Na2⁢Co2⁢TeO6 is stabilized at a rate of 𝜕𝑇N/𝜕𝑝c=0.28⁢(5) K/GPa. Further, failure of the Grüneisen scaling at low temperatures around 𝑇cr≃7.5K demonstrates the presence of competing energy scales. In contrast to an only weak field dependence of the anomaly at 𝑇N, a broad hump at 𝑇cr(𝐵=0T) evolves into a sharp peak at high fields applied 𝐵∥𝑐. Our magnetostriction data show that a kink in the magnetization at 𝐵C≃4.6T is accompanied by an inflection point in the field-induced length changes, which is likely related to weak unequal spin canting. All observed phenomena leave their signatures in the magnetoelastic phase diagram as constructed by our experimental results.
Online veröffentlicht am 18. September 2025
Im Titel sind die Ziffern 2 und 6 tiefgestellt
Gesehen am 24.02.2026